(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
This article explores the theoretical and methodological aspects of innovative approaches in the professional education of physical education teachers. These approaches include the latest technologies, teaching methodologies, and assessment methods that together form the modern educational paradigm. They open up new opportunities for development and self-realization of students, as well as contribute to increasing the efficiency of the educational process. Innovative approaches pave the way for creating an adaptive and inclusive educational system capable of meeting the needs of modern society and promoting a healthy lifestyle. Innovations enable physical education teachers to be more prepared for the challenges of modernity, effectively implement changes in the educational process, and create a learning environment that fosters the development of critical thinking and creativity. Various types of innovative approaches, their essence, and specifics were analyzed, and a complex of innovative teaching methods and technologies aimed at forming key competencies of future physical education teachers was proposed. The importance of innovative approaches for improving the quality of educational services, adapting to labor market requirements, and integrating into the global educational space was highlighted. Particular attention is given to the competency-based approach, which is aimed at forming the necessary skills and abilities that meet the modern labor market demands. Recommendations for further scientific research on the effectiveness and impact of innovative approaches in the professional education of physical education teachers at different levels of education and in various socio-cultural contexts have also been developed. This research may include the analysis of the implementation of innovative technologies such as virtual reality and interactive platforms, which can provide a deeper immersion in the educational material and increase student motivation. Additionally, an important aspect is the study of the impact of innovations on the formation of intercultural competence and global thinking among physical education teachers, which is necessary for effective work in the international educational space.